Sex ratios, virginity, and local resource enhancement in a quasisocial parasitoid - Kapranas, Apostolos; Hardy, Ian C.W.; Tang, Xiuyun; Gardner, Andy; Li, Baoping (Wiley, 2016)
Sclerodermus harmandi (Buysson) (Hymenoptera: Bethylidae) is an economically beneficial 2 species of parasitoid wasp that has an unusual level of sociality: groups of female foundresses 3 reproduce on a single host and exhibit cooperative post-ovipositional brood care. The 4 beneficial effects females have on each other’s reproductive success provide, via the theory 5 of local resource enhancement (LRE), an explanation for their female-biased progeny sex 6 ratios, which is part of the same framework for understanding sex-ratio evolution as the more 7 often invoked theory of local mate competition (LMC). Here we show that S. harmandi sex 8 ratios are over-dispersed, with high variance largely attributable to the common occurrence 9 (60%) of developmental mortality. Developmental mortality is also positively associated with 10 the proportion of broods which contain only females at emergence (virgin broods). Virginity 11 is more common when broods are produced by fewer foundresses. Virginity is expected to be 12 disadvantageous under LRE, as it is under LMC, but theory for LRE is less extensively 13 developed. We suggest approaches for the development of LRE theory, in particular using 14 models of ‘population elasticity’ in which the intensity of kin competition is reduced because 15 extra resources are available to local populations that are more cooperative. For S. harmandi, 16 such extra resources may include large hosts that can only be successfully utilized if multiple 17 foundresses cooperate.